Anaerobic Capacity is Associated with Metabolic Contribution and Mechanical Output Measured during the Wingate Test - Poli, Rodrigo Araujo Bonetti De [UNESP] (2021)
The study aimed to investigate the relationship between anaerobic capacity, mechanical and anaerobic contribution during the 30-s Wingate Anaerobic Test (30sWAnT). After familiarization, fifteen, male recreational mountain biking practitioners underwent the following sequence of tests: 1) a graded exercise test to determine maximal oxygen uptake and associated intensity (iV˙ O2max);2 and 3) supramaximal exhaustive effort at 115% of iV˙ O2max and 30sWAnT, performed randomly. The glycolytic and phosphagen pathways measured during the supramaximal effort were significantly correlated with peak power (r = 0.85; p < 0.01 and r = 0.57; p = 0.02, respectively), mean power (r = 0.78; p < 0.01 and r = 0.69; p < 0.01, respectively), and total work (r = 0.78; p < 0.01 and r = 0.69; p< 0.02, respectively) measured during the 30sWAnT. A significant correlation was also found between anaerobic capacity and peak power (r = 0.88; p < 0.01), mean power (r = 0.89; p < 0.01), and total work (r = 0.89; p < 0.01). Additionally, anaerobic capacity estimated during the supramaximal effort and the anaerobic contribution measured during the 30sWAnT were not different (p = 0.44) and presented significant good reliability and association (ICC = 0.84; p = 0.001) and good agreement, evidenced by the mean of differences and 95% limits of agreement near to zero (mean bias = 0.11). The results suggest that glycolytic and phosphagen capacity were associated with mechanical performance in the 30sWAnT. In addition, anaerobic contribution during the 30sWAnT seems to be valid for estimating anaerobic capacity in recreational mountain bike cyclists, as well as to estimate the glycolytic and phosphagen contributions.